Virtual surgical analysis: long-term cone beam computed tomography stability assessment of segmental bimaxillary surgery. Issue 9 (September 2022) - Holte, M.B.; Diaconu, A.; Ingerslev, J.; Thorn, J.J.; Pinholt, E.M.
Abstract: The assessment of the stability of orthognathic surgery is often time-consuming, relies on manual re-identification of anatomical landmarks, and has been based on short-term follow-up. The purpose of this study was to propose and validate a semi-automated approach for three-dimensional (3D) assessment of the long-term stability of segmental bimaxillary surgery. The approach was developed and validated using cone beam computed tomography scans obtained at 2 weeks and 2 years postoperative. The stability of the surgical outcome was calculated as 3D translational and rotational differences between the short- and long-term postoperative positions of the individual bone segments. To evaluate reliability, intra-class correlation coefficients were calculated at a 95% confidence interval on measurements of two observers. Ten class II and III patients (six male, four female; mean age 24.4 years), who underwent a combined three-piece Le Fort I osteotomy, bilateral sagittal split osteotomy, and genioplasty, were included in the study. Intra- and inter-observer reliability were excellent (range 0.82–0.99). The range of the mean absolute difference of the intra- and inter-observer translational and rotational measurements were 0.14 mm (0.13)–0.44 mm (0.50) and 0.20° (0.16)–0.92° (0.78). The approach has excellent reliability for 3D assessment of long-term stability of segmental bimaxillary surgery.